Mechanical Behavior of Poorly Graded Sandy Soil Using Compaction and Direct Shear Tests - Rivianto, Arif; Candra, Agata Iwan; Ali, Mahardi Kamalika Khusna; Kottama, Gilang Wahyu; Prasetyo, Mokhamat Wildan; Budiawan, Muhamad Rizal Agus Joko; Rohman, Muhammad Rifqi Fatkhur; Taufani, Muhammad Sousa (Jurnal Teknik Sipil, 2023)
Soil has important elements for living things as a place to live, building materials and planting media. The diversity of soil properties has been understood in various fields of science. Soil resistance greatly affects the stability and carrying capacity of the soil in civil buildings. Soil samples were taken from Sidorejo Village, Nganjuk Regency, which are classified as poorly graded sandy soils (SP). Many investigations have been made regarding the physical and mechanical properties of soil by examining compaction and shear strength. However, there are still many researchers who do not know the soil mechanical behavior in detail regarding soil (SP). The compaction test was carried out using the Standard Proctor Test method with the addition of 2.5% water to each sample, followed by a shear strength test using the Direct Shear Test method from compaction samples with maximum wet weight. This study aims to determine the mechanical behavior of poorly graded sand (SP) on shear strength. The shear strength test obtained a cohesion value of 2.0305 kPa and a shear angle of 28.892°. Based on the research results, soil mechanical properties (SP) can be used as a reference for construction on the same soil type and soil classification.